2021
DOI: 10.1099/jgv.0.001545
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the outcomes of COVID-19 – does the current model of an acute respiratory infection really fit?

Abstract: Although coronavirus disease 2019 (COVID-19) is regarded as an acute, resolving infection followed by the development of protective immunity, recent systematic literature review documents evidence for often highly prolonged shedding of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in respiratory and faecal samples, periodic recurrence of PCR positivity in a substantial proportion of individuals and increasingly documented instances of reinfection associated with a lack of protective immunity. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
17
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 105 publications
3
17
0
4
Order By: Relevance
“…We found that SARS-CoV-2 gRNA persisted in the presence of RDV, suggesting a long halflife that may reflect the high secondary structure of the RNA genome that could render it refractory to the action of nucleases (Simmonds et al, 2021). smFISH revealed complex dynamics of gRNA and sgRNA expression that resulted in a rapid expansion of sgRNA (peaking at 8hpi), followed by a shift towards the production of gRNA (24 hpi), results that were confirmed by RNAseq.…”
Section: Discussionsupporting
confidence: 60%
“…We found that SARS-CoV-2 gRNA persisted in the presence of RDV, suggesting a long halflife that may reflect the high secondary structure of the RNA genome that could render it refractory to the action of nucleases (Simmonds et al, 2021). smFISH revealed complex dynamics of gRNA and sgRNA expression that resulted in a rapid expansion of sgRNA (peaking at 8hpi), followed by a shift towards the production of gRNA (24 hpi), results that were confirmed by RNAseq.…”
Section: Discussionsupporting
confidence: 60%
“…Research conducted at the Nuffield Department of Medicine at the University of Oxford purports that many of the cases of reinfection may actually be reactivation 5. Mossong points out that coronaviruses give long infections and their large genomic structures could cause them to remain in the body at low enough levels to remain undetected but ready to strike once more.…”
Section: Reinfection or Reactivation?mentioning
confidence: 99%
“…This may be because the importance of removing redundant information and analyzing solely the contribution of base order to folding energy, was not fully appreciated. Even those who have employed the same technology have expressed puzzlement at the "biological purpose" of so much "pervasive RNA secondary structure in the genomes of SARS-CoV-2 and other coronaviruses" (Simmonds 2020a) and regret the "poorly understood RNA structure-mediated effects on innate and adaptive host immune responses" (Simmonds et al, 2020). Thus, we have here repeated and expanded on past clarifications (Forsdyke 2007a;Xu et al, 2007; of the conceptual basis of a technology that has contributed to the understanding of a many biological problems other than viral infections (Forsdyke 2016).…”
Section: Discussionmentioning
confidence: 99%